2016
DOI: 10.1515/hmbci-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

The role of ghrelin in the regulation of glucose homeostasis

Abstract: Ghrelin is a 28-amino acid (aa) stomach-derived peptide discovered in 1999 as the endogenous ligand for growth hormone secretagogue-receptor (GHS-R). Ghrelin-producing cells constitute a distinct group of endocrine cells dispersed throughout the gastric mucosa and to a lesser extent in the small intestine and the endocrine pancreas. Ghrelin plasma levels rise during fasting and chronic caloric restriction to stimulate food intake and fat storage and to prevent life-threatening falls in blood glucose. Plasma gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 59 publications
0
47
1
2
Order By: Relevance
“…Thus, exogenous desacyl ghrelin administration acts as a potent insulin secretagogue, whereas acylated ghrelin decreases glucose-induced insulin release and increases glucose levels in both humans and rodents4445. In line with these observations, genetic, immunological, and pharmacological blockade of ghrelin signalling enhances glucose-stimulated insulin secretion and improves peripheral insulin sensitivity46. Thus, it seems plausible that ghrelin changes after sleeve gastrectomy also contribute, at least in part, to the observed improvement in insulin sensitivity after sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, exogenous desacyl ghrelin administration acts as a potent insulin secretagogue, whereas acylated ghrelin decreases glucose-induced insulin release and increases glucose levels in both humans and rodents4445. In line with these observations, genetic, immunological, and pharmacological blockade of ghrelin signalling enhances glucose-stimulated insulin secretion and improves peripheral insulin sensitivity46. Thus, it seems plausible that ghrelin changes after sleeve gastrectomy also contribute, at least in part, to the observed improvement in insulin sensitivity after sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 78%
“…By contrary, ghrelin concentrations are negatively correlated with BMI in humans and insulin resistance29, the observed increased levels of leptin and decrease levels of ghrelin might be associated to the fat mass depots in obese groups(Table 1). Reports have indicated that insulin could induce leptin secretion and production event though body fat is the determinant factor of circulating leptin30.…”
Section: Discussionmentioning
confidence: 98%
“…Aside from hyperphagia and obesity, ghrelin is also extensively involved in the regulation of glucose metabolism [279]. Acyl ghrelin chiefly has hyperglycemic effects [280] and promotes insulin resistance [281,282], acting on both pancreatic islets to suppress insulin secretion [283] and on hepatocytes to stimulate glucose output [284], whereas des-acyl ghrelin may counteract the hyperglycemic effects of acyl ghrelin and enhance insulin sensitivity [282,284,285,286].…”
Section: Metabolic Diseasementioning
confidence: 99%